Pseudodifferential operators with complex arguments and Cauchy problem - Dubinskii, J. (Mathematical Modelling and Analysis, 1996)
“Pseudodifferential operators with complex arguments and Cauchy problem”Mathematical Modelling and Analysis, 1(1), p. 15.First Published Online: 14 Oct 2010